Quantitative Study of Antibiotic Usage in Pneumonia Patients: Systematic Literature Review - Delina Hasan; Yardi Saibi; Nelly Suryani; Muhammad Yanis Musdja; Vidia Arlaini; Dzdzikra D.A Dzdzikra D.A (Eduvest - Journal of Universal Studies, 2024)
Pneumonia caused more than 2,56 million deaths in 2017 worldwide. With the high number of pneumonia sufferers, the use of antibiotics will also increase. This study aims to describe the quantity of antibiotic use in pneumonia patients using the Systematic Literature Review method. The literature search was conducted through the PubMed, Sciencedirect, Mendeley, BMC, and Google Scholar databases. The literature used is a journal of the last 10 years that discusses the use of antibiotics in pneumonia patients calculated by the ATC/DDD system. Of the total 19 journals included in the study, 8 journals were from Indonesia. A total of 5 journals discussed antibiotics used in CAP (Community-Acquired Pneumonia), 2 journals in HAP (Hospital-Acquired Pneumonia), 2 journals in VAP (Ventilator-Associated Pneumonia), 2 journals were non-specific, and the remainder covered several types of pneumonia. The class of antibiotics with the highest DDD value is fluoroquinolones, with an average use of 41,81 DDD/100 patient-days; 17,29 DDD/100 bed days; and 0,0696 DDD/1000 inhabitants per day, and third-generation cephalosporins, with an average use of 15,86 DDD/100 patient-days and 28,31 DDD/100 bed days. The antibiotic with the highest DDD value was levofloxacin, with an average use of 31,29 DDD/100 patient-days; 12,22 DDD/100 bed days; and 0,0612 DDD/1000 inhabitants per day, and ceftriaxone, with an average use of 12,51 DDD/100 patient-days and 26,33 DDD/100 bed days. The most widely used antibiotics in the treatment of CAP and HAP are third-generation cephalosporins, while penicillin is the most commonly used in VAP.